1998
DOI: 10.1038/sj.bmt.1701364
|View full text |Cite
|
Sign up to set email alerts
|

Post-chemotherapy and cytokine pretreated marrow stromal cell layers suppress hematopoiesis from normal donor CD34+ cells

Abstract: Summary:Marrow stromal layers were used to investigate the potential role of negative regulators produced by the marrow microenvironment as one potential cause of hematopoietic suppression after chemotherapy and cytokines. Stromal layers were established from marrow of normal or prechemotherapy donors and breast cancer patients after hematological recovery from one cycle of 5-fluorouracil, leucovorin, doxorubicin, and cyclophosphamide and GM-CSF or PIXY321 (GM-CSF/IL-3 fusion protein). Normal donor CD34 + cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 34 publications
(45 reference statements)
3
18
0
Order By: Relevance
“…Presence of N-cadherin positive cells in CD271 and RossetteSep fractions is intriguing in the light of recent reports showing that spindle-shaped, N-cadherin + osteoblasts (SNO) form niches supporting hematopoietic cells development [40]. Preservation or even enrichment of SNO precursor cells before subsequent transplantation could be of great importance for reconstitution of hematopoietic niches after myeloablative therapies which negatively affect bone marrow microenvironment [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of N-cadherin positive cells in CD271 and RossetteSep fractions is intriguing in the light of recent reports showing that spindle-shaped, N-cadherin + osteoblasts (SNO) form niches supporting hematopoietic cells development [40]. Preservation or even enrichment of SNO precursor cells before subsequent transplantation could be of great importance for reconstitution of hematopoietic niches after myeloablative therapies which negatively affect bone marrow microenvironment [41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that stromal cell lines support HSC survival in long-term cultures, emphasizing a collaborative mode of interaction between donor cells and the recipient BM microenvironment [27][28][29]. However, numerous studies have pointed out that the expressions of cytokines and cell-surface ligands of both HSCs and stromal cells were altered by the interaction itself and varied in different experimental conditions [29][30][31].…”
Section: Physiological Considerationsmentioning
confidence: 99%
“…Cellular homing to the host BM is mediated by a variety of molecular interactions and is influenced by the phenotype of Askenasy,Farkas 510 the transplanted cells and their stage in the cell cycle [11-16, 19, 42-45]. Then, the cells interact with the BM stromal microenvironment and the extracellular matrix in a complex manner, as suggested by the large number of ligands and receptors shown to affect seeding and engraftment [11,16,[21][22][23][24][25][26][27][28][29]. Despite the identification of several important molecular mechanisms of homing and seeding, much remains unknown about these early events of engraftment.…”
Section: Physiological Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…So it might be desirable to repair or replace a damaged bone marrow stromal compartment possibly by transplanting donor stromal cells [4][5][6][7]. Given the fact that donor-derived stromal cells do not engraft following conventional HSCT due to the limited number of stromal cells present in a typical allograft even having a competitive advantage over the damaged recipient's stroma, donor stromal cell engraftment could be achieved by transplanting a large number of MSCs that had been expanded in culture [8].…”
Section: Introductionmentioning
confidence: 99%